2019
DOI: 10.1080/17515831.2019.1656908
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ultrafine precipitates and its influence on wear mechanism in cryoprocessed high nitrogen martensitic steel

Abstract: Development of the space engines with liquid propellants necessitates the use of bearings of high quality. During recent years, a new family of high strength corrosion resistant steels, with partial replacement of carbon by nitrogen, known as high nitrogen steels were developed having higher impact strength and fracture toughness coupled with high hardness for antifriction bearing of cryopumps in rocket. In this research work, wear characteristics of cryogenically treated high nitrogen martensitic stainless st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…When the austenite grains grow up, the expanding grain boundary will bend when encountering the second phase particles, which leads to the increase of interface energy and impeded the migration of the grain boundary. [ 19 ] A lot of alloy elements in the tested steel and the carbon content gradient of the carburized layer attributed to be responsible for the variation in the fraction of precipitates pinned austenite grain boundary. The statistical results in Table 1 also confirmed that the fraction of precipitates gradually decreased with the increase of the case layer depth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the austenite grains grow up, the expanding grain boundary will bend when encountering the second phase particles, which leads to the increase of interface energy and impeded the migration of the grain boundary. [ 19 ] A lot of alloy elements in the tested steel and the carbon content gradient of the carburized layer attributed to be responsible for the variation in the fraction of precipitates pinned austenite grain boundary. The statistical results in Table 1 also confirmed that the fraction of precipitates gradually decreased with the increase of the case layer depth.…”
Section: Resultsmentioning
confidence: 99%
“…[7,14,18] Simultaneously, it has also been revealed that nitrogen contributes to the quantitative control of the chromium carbide precipitates formed during tempering. [19,20] Xu et al [18] demonstrated that nitrogen addition could not only effectively reduce the amount and size of coarse carbides, but also significantly refine the prior austenite grain size. In addition, the appearance of Cr-rich nitrides induced by the addition of N corresponded to a high N concentration and high The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/srin.202100849.…”
Section: Introductionmentioning
confidence: 99%